2018
DOI: 10.29359/bjhpa.10.1.07
|View full text |Cite
|
Sign up to set email alerts
|

Athletes with disability in the light of positive psychology

Abstract: Background:The purpose of the study was to describe selected aspects of good life in Polish paralympic athletes in the light of positive psychology. Good life category was investigated in such dimensions as satisfaction with life, resilience, personal values and courage.Material/Methods: The project involved a study group of 30 disabled athletes (M = 26.5 years of age) practising skiing, cycling, swimming, fencing, basketball, and a control group consisting of 30 healthy young adults (M = 25.9 years of age) do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…We also found a high value for resilience. This data reinforces the literature that states athletes with disabilities show significant levels of resilience [ 42 , 43 , 44 , 86 ]. Hariharan et al [ 89 ] found that resilient people with disabilities had higher emotional intelligence and more positive perceptions of their environment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also found a high value for resilience. This data reinforces the literature that states athletes with disabilities show significant levels of resilience [ 42 , 43 , 44 , 86 ]. Hariharan et al [ 89 ] found that resilient people with disabilities had higher emotional intelligence and more positive perceptions of their environment.…”
Section: Discussionsupporting
confidence: 90%
“…Participation in sports by people with disabilities has implications for resilience, access to social support, opportunities, and meaningful social experiences for people who faced traumatic injuries [ 42 ]. Athletes with disabilities show significant levels of resilience [ 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although physically disabled athletes have diverse disabilities in trunks/limbs, they engage in diverse competitive sports such as basketball, goalball, rugby, athletics, archery, shooting, powerlifting, and many others ( IPC, 2021 ). Research suggests that engaging in competitive sports is beneficial to physically disabled athletes’ cognitive function ( Di Russo et al, 2010 ), resilience and courage ( Sikorska & Gerc, 2018 ), self-esteem ( Van de Vliet, Van Biesen & Vanlandewijck, 2008 ), and social function ( Smith, Bundon & Best, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Personality and self-control can be mediated with self-efficacy (Sikorska and Gerc, 2018). When considering the self-efficacy and selfregulation theories of Badura, a claim could be made that self-control affects self-efficacy and there exists a significant positive correlation between the two (Bandura, 1978).…”
Section: Table 1 Frequency Of Genotypes and Alleles Of The Dat1 Gene mentioning
confidence: 99%